Intelligent microwave and PIR sensor system for energy efficiency in buildings / M. F. Jamburi, F. Sulaiman and A. Ahmad - Jamburi, M. F.; Sulaiman, F.; Ahmad, A. (UiTM Press, 2013)
A lot of an electrical energy is wasted everyday due to human attitudes. This paper introduces an alternative way of saving electrical energy by using an intelligent method that have been designed suitable for application in houses and offices. Generally, the system is based on a sensor as a supervisory control in order to organize the electrical energy in houses or room intelligently. In this project fuzzy logic is introduced as a controller for the system. A fuzzy logic controller will make a decision before sending a signal to an actuator either switching on or off the electrical energy. An electrical energy is automatically turned on since the sensor detect the present of human in form of microwave motion and thermal radiation [8]. On the other hand, electrical energy is automatically turned off if there is no human present around the area that it covers. Therefore, the purpose of this project is to effectively control artificial electrical appliances in a smart way for energy saving and energy efficiency in rooms, houses and offices.